Pendampingan Strategi Branding melalui Perancangan Desain Logo bagi UMKM Susu Kambing Etawa di Desa Simo, Kecamatan Slahung, Kabupaten Ponorogo - Nurcholis, Agung; Zaen, Azhar Amir; Danis, Ahmad (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Branding plays an important role in increasing the competitiveness of MSMEs, especially in the food industry. However, many MSMEs, including Etawa goat milk businesses, do not yet have a strong visual identity. This service aims to design a logo that matches the characteristics of Etawa goat milk products and evaluate its impact on consumer appeal. Using a mixed-method approach, this Service applies thematic analysis to understand MSME owners' preferences for branding and logo design, as well as quantitative analysis to measure consumer visual perception through a Likert scale (1-5). The results of the Service show that MSME owners have a primary preference for a circular logo that can be easily attached to the packaging bottle. In addition, owners prefer striking colors and adding additional elements such as slogans and telephone numbers. The visual perception test conducted on 40 respondents showed that the visual appeal aspect obtained an average score of 4.3/5, readability 4.3/5, and relevance to the product 4.4/5. The conclusion of this Service confirms that a logo designed in a participatory manner can improve MSME branding more effectively. As a recommendation, MSMEs are advised to not only use logos as visual identities but also integrate them into digital marketing strategies to be more competitive in the market.